2019
DOI: 10.1101/860015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical plasticity of the ECM directs invasive branching morphogenesis in human mammary gland organoids

Abstract: 11Although branching morphogenesis is central for organogenesis in diverse organs, the underlying 12 self-organizing principles have yet to be identified. Here, we show that invasive branching 13 morphogenesis in human mammary organoids relies on an intricate tension-driven feedback 14 mechanism, which is based on the nonlinear and plastic mechanical response of the surrounding 15 collagen network. Specifically, we demonstrate that collective motion of cells within organoid 16branches generates tension that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…MEP contractility is a key physiological function of mammary epithelia that is attainable via microcontainer culture. MEP cells, along with fibroblasts, can deform the matrix, such as by contracting collagen ( Nielsen et al., 2003 ), and it has been shown that such contractions may be mediated through MEP motility ( Buchmann et al., 2019 ). The pulsatility of contractions seen in microcontainers appears to be novel.…”
Section: Discussionmentioning
confidence: 99%
“…MEP contractility is a key physiological function of mammary epithelia that is attainable via microcontainer culture. MEP cells, along with fibroblasts, can deform the matrix, such as by contracting collagen ( Nielsen et al., 2003 ), and it has been shown that such contractions may be mediated through MEP motility ( Buchmann et al., 2019 ). The pulsatility of contractions seen in microcontainers appears to be novel.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have revealed that inclusion of the inflammatory cytokine TNF-alpha during culture (probably mimicking proregenerative signals) increases organoid formation efficiency with a corresponding localization of YAP to the nucleus, suggesting that YAP may also receive inputs from medium components [16]. These experiments also open the door to further investigations on the importance of mechanical processes during organoid formation and their control by the surrounding matrix and neighboring cells [103,104].…”
Section: Exchange Of Signals Between Cells and Scale Of Interactionsmentioning
confidence: 91%
“…These resemble miniaturized and simplified organs with realistic micro-anatomy, and feature collective motility/invasion behaviour directing cells to migrate and proliferate to form ordered, branched structures. 37,38 Controlling organoid morphology is a sought-after goal, which has been mostly interpreted as requiring spatiotemporal control of gene expression, for which optogenetic approaches have been suggested. 39 Yet, the spatiotemporally-localized application of photochemical compounds offers an alternative, in which the possibility of instantaneous cellular response to stimulus is highly attractive for temporally-precise control.…”
Section: Sbtub Photocontrol In 3d Organoids Enables Spatially-targetementioning
confidence: 99%
“…39 Yet, the spatiotemporally-localized application of photochemical compounds offers an alternative, in which the possibility of instantaneous cellular response to stimulus is highly attractive for temporally-precise control. Based on the good performance of SBTubA4P in 2D cell culture, we assessed whether SBTubA4P can be controlled similarly precisely in a 3D organoid model, aiming to manipulate organoid development by locally interfering with the invasion of individual branches during the elongation phase 38 .…”
Section: Sbtub Photocontrol In 3d Organoids Enables Spatially-targetementioning
confidence: 99%